PEMBINAAN SPIRITUALITAS MAHASISWA MELALUI IBADAH KAMPUS BERTEMA “SEVEN CAPITAL SIN IN HISTORY” DI STIP MARUNDA - Anggi Maringan Maringan Hasiholan (Penerbit Widina, Widina Media Utama, 2026)
This Community Service program aimed to foster students’ spirituality through a campus worship service themed “Seven Capital Sin in History” at STIP Marunda. The program was grounded in the need for spiritual formation among maritime students who are being prepared not only with technical competence but also with integrity, self-control, discipline, responsibility, and spiritual maturity. The implementation method employed an educational-reflective approach through preaching, moral value internalization, spiritual reflection, activity evaluation, and follow-up formation. The theme of the seven capital sins was used as a theological and moral framework to help students recognize destructive tendencies within themselves, including pride, greed, lust, envy, gluttony, wrath, and spiritual sloth. The results indicate that campus worship functions as an educational, reflective, and transformative space for student formation. Students were guided to understand spirituality not merely as a ritual activity, but as the foundation for character development, personal integrity, social awareness, and professional readiness. The activity contributed to the growth of reflective awareness, contextual moral understanding, self-control, spiritual discipline, and commitment to practicing Christian values in academic and social life. Therefore, campus worship can serve as a relevant and sustainable strategy for strengthening students’ spirituality and character formation.